Discussions On The Relationship Between Technology And Bioethics: An Analysis Of The Film I Am Mother From The Perspective Of Medical Ethics - Fatma Ay; Selver Namli; Sümeyra Dinler; Fatmanur Kaman; Hatice Çetinkaya Şenli (JOURNAL OF BIOTECHNOLOGY AND STRATEGIC HEALTH RESEARCH, 2026)
Objective: The technology, especially in the fields of health and medicine, have also become a source of ethical concern. This article aims to clarify the ethical principles and ethical dilemmas that, in the film I Am Mother, lead viewers to reflect on reproduction, mother–infant attachment, eugenics, and the right to life in the future visualized in the film. Methods: A descriptive analysis method was used in the study. The analysis was conducted through the themes of universal ethical principles and the principles of medical ethics. When all images and dialogues were examined, the presence of the universal ethical principles of beneficence, nonmaleficence, justice, equality, and autonomy, as well as the medical ethics principles of honesty and respect for human dignity, was identified. Results: Overall, I Am Mother offers a provocative bioethical reflection by prompting thought on these ethical principles in the context of artificial intelligence governance, human identity, and survival. It also raises the question of whether emotional manipulation, deception, and the imposition of an artificial environment constitute harm, despite an intended protective rationale. Conclusion: The film critically illustrates how autonomy may be nurtured or weakened in relationships involving advanced artificial intelligence. At a time when technology increasingly intersects with human life and moral structure, films provide examples of contemporary challenges in the field of bioethics. In this way, they contribute to decision-making processes in matters where ethical dilemmas may arise.